2017
DOI: 10.1002/1873-3468.12758
|View full text |Cite
|
Sign up to set email alerts
|

Noncentrosomal microtubules regulate autophagosome transport through CAMSAP2‐EB1 cross‐talk

Abstract: Microtubules (MTs) play essential roles in many steps of autophagy, an important degradation pathway in the maintenance of cellular homoeostasis. In many cells, MT networks are comprised of centrosomal MTs and noncentrosomal MTs. However, it is unknown whether noncentrosomal MTs and its binding proteins are involved in autophagy. Here, we show in HeLa cells that calmodulin-regulated spectrin-associated protein 2 (CAMSAP2), a noncentrosomal MT minus-end stabilizing protein, regulates retrograde transport of aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…24 Recently, vimentin was shown to be transported bidirectionally along the microtubule cytoskeleton, 43 and CAMSAP family proteins regulate the trafficking of cargo through microtubule dynamics. 16 CAMSAP3 might probably interact with vimentin in this event. Proteomic analysis also indicated an interplay among CAMSAP3, ERK, and vimentin (Figure 5), suggesting that vimentin is an intermediate scaffold for CAMSAP3-regulated ERK activity.…”
Section: F I G U R E 5 Camsap3 Regulates Erk Activity Via Vimentin the Top Ten Lists Of Proteins Possibly Interacting With (A) Erk And (Bmentioning
confidence: 96%
See 2 more Smart Citations
“…24 Recently, vimentin was shown to be transported bidirectionally along the microtubule cytoskeleton, 43 and CAMSAP family proteins regulate the trafficking of cargo through microtubule dynamics. 16 CAMSAP3 might probably interact with vimentin in this event. Proteomic analysis also indicated an interplay among CAMSAP3, ERK, and vimentin (Figure 5), suggesting that vimentin is an intermediate scaffold for CAMSAP3-regulated ERK activity.…”
Section: F I G U R E 5 Camsap3 Regulates Erk Activity Via Vimentin the Top Ten Lists Of Proteins Possibly Interacting With (A) Erk And (Bmentioning
confidence: 96%
“…Recently, the calmodulin-regulated spectrin-associated protein (CAMSAP) family has gained increasing attention in cancer cell biology. 16 CAMSAPs, non-centrosomal microtubule minus-end binding proteins, are required for maintaining microtubule organization and cellular morphogenesis. [16][17][18] The CAMSAP family comprises CAMSAP1, CAMSAP2, and CAMSAP3, and we reported that CAMSAP3 maintains the epithelial state of lung cancer-derived cells, preventing them from epithelialmesenchymal transition (EMT), which is a form of cell changes associated with cancer progression.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, it is worth noting that CAMSAP2 recognizes MT minus ends and tethers them to the cis ‐Golgi membrane to protect them from depolymerization, independent of γ‐TuRC‐mediated MT nucleation at the cis ‐Golgi . Additionally, CAMSAP2 is known to cooperate with EB1 and EB3 at the Golgi apparatus to regulate MT growth dynamics and Golgi reorientation . Our findings indicate that IFT20 is required for polarized and continuous MT growth and for Golgi reorientation during collective invasion.…”
Section: Discussionmentioning
confidence: 78%
“…is known to cooperate with EB1 and EB3 at the Golgi apparatus to regulate MT growth dynamics and Golgi reorientation. 53,54 Our findings indicate that IFT20 is required for polarized and continuous MT growth and for Golgi reorientation during collective invasion. Thus, there might be a link between IFT20 and CAMSAP2 in regulating MT dynamics at the Golgi apparatus, required for proper organization of Golgi-associated MTs and Golgi polarity during collective invasion.…”
Section: Furthermore Ift20 Promotes Invasion Of Sw480 Cells (Expressingmentioning
confidence: 73%